Alterations of fractional anisotropy and white matter integrity in irritable bowel syndrome: a systematic review and meta-analysis of diffusion tensor imaging studies - Asadi Anar, Mahsa; Hassanpour Adeh, Aydin; Peiravi, Samira; Imani Porshokouh, Alireza; Rezazadeh Shojaee, Seyedeh Sara; Najafi, Farnaz; Pishkari, Yasamin; Rahimi, Arash; Karami, Shaghayegh (Frontiers in Neuroscience, 2024)
Background and aimThe neurological processes responsible for irritable bowel syndrome (IBS) pathophysiology and its clinical potentials are not fully understood. The current study aimed to examine white matter microstructural abnormalities and the reasons behind white matter impairment in individuals with irritable bowel syndrome by performing a meta-analysis of diffusion tensor imaging studies.MethodsPubMed, Scopus and Web of Science were searched until April 2024. Chosen articles based on our defined eligibility criteria were extracted for the data relating to fractional anisotropy and brain connectivity. Webplot digitizer was used to extract digital data. We used the latest version of STATA(ver18) to meta-analyze the data. Quality assessment of studies was done using a critical appraisal tool. Egger’s test for minor study effects assessed the publication bias.Results543 IBS cases and 472 healthy controls were included in this study. The mean age of the case and control group was 35.2 ± 17.4 and 33.6 ± 15.8 (mean ± SD), respectively. There was no statistically significant difference in age between groups (p > 0.05). Analyzed Standard mean difference using a fixed model for Fractional anisotropy of regions of interest (ROI) associated with sensory processing, such as the thalamus, insula, primary somatosensory cortex, dorsal cingulum and the fornix in selected studies showcased decreased white matter interactivity in case group however this decrease was not statistically different [SMD −88, 95%CI (−1.32, −0.44), p > 0.05].ConclusionFurther investigation is necessary to ascertain whether the modified structural connectivity mentioned in this study is a contributing factor to IBS, an outcome of the condition, a risk factor for it, or, more probably, a consequence of a mutually influential relationship between the changes observed in the white matter tract and IBS symptoms.